When Do Work-Family Policies Work? Unpacking the Effects of Stigma and Financial Costs for Men and Women - Thébaud, Sarah; Pedulla, David S. (Work and occupations, 2022)
Work-family policies—such as parental leave and flextime—can help to facilitate gender equality in workplaces and in families. But policy use is typically low, varies significantly from one workplace to another, and is often more prevalent among women than men. Extant research suggests that flexibility stigma—workplace norms that penalize workers for utilizing policies that facilitate non-work demands—as well as the financial costs associated with policy use, contribute to this pattern. However, previous studies have been largely correlational in nature, and have had difficulty assessing how these factors may interact with one another to shape gendered patterns of policy use. In this study, we offer novel causal traction on this set of issues. Using an original, population-based survey experiment, we examine how the salience of flexibility stigma and financial costs affect men's and women's intentions to use work-family policies. We find that these factors exert a large direct effect on men's and women's intentions to use work-family policies. Moreover, the gender gap in parental leave use intentions is large in workplace contexts with high flexibility stigma and high financial costs, but this gap narrows significantly under more favorable conditions. Findings point to the importance of organizational contexts and policy design in shaping work-family policy use and, in turn, gender inequality.